A Methodical Review of the Relationship Between Legal Frameworks and Social Behavior - Maulina sintia; Hasti Kumala; Arnesto (Yayasan Cinta Negara, 2025)
Legal frameworks play an important role in shaping people's behaviour through regulation, incentives and value internalization mechanisms. This study aims to provide a systematic review of how law operates as a social instrument in influencing individual and collective action in various social contexts. Using an interdisciplinary approach that includes the perspectives of legal sociology, normative theory, and public policy studies, this study analyzes relevant academic literature in the last two decades. The review identifies three main mechanisms of law's influence on people's behavior: (1) law as a means of control through formal sanctions and regulations, (2) law as an agent of social change that instills new values and norms, and (3) law as part of the social contract that reflects societal consensus. In addition, this study also discusses factors that influence legal effectiveness, including institutional legitimacy, enforcement capacity, and local cultural and political dynamics. The results of this study show that the success of the legal framework in shaping behavior is highly dependent on the compatibility between legal norms and the social values of the community. Therefore, a deep understanding of the relationship between law and social behavior is crucial in the formulation of effective and sustainable legal policies